'Male' and 'female' in the quechua language (ACME, 2022)
The article illustrates the main Quechua language features related to the distinction between ‘male’ and ‘female’. The first part indicates how Quechua encodes this distinction through the lexicon, focusing on kinship terms; the second part examines the nouns, adjectives and verbs indicating people, behaviours and habits considered typically feminine or masculine. Both the first part and the second are aimed at highlighting some socio-cultural factors associated with the linguistic distinction between the female and male genders.
Keywords: semantics; lexicon; gender; quechua; kinship; stereotypes